The Efficacy of Amifostine against Multiple-Dose Doxorubicin-Induced Toxicity in Rats - Jaćević, Vesna; Dragojević-Simić, Viktorija; Tatomirović, Željka; Dobrić, Silva; Bokonjić, Dubravko; Kovačević, Aleksandra; Nepovimova, Eugenie; Vališ, Martin; Kuča, Kamil (International journal of molecular sciences, 2018)
Amifostine is well known cytoprotector which is efficient when administered before a wide range of antineoplastic agents. The aim of our study was to investigate amifostine effects on doxorubicin-induced toxic changes in rats. Amifostine (75 mg/kg ip) was given 30 min before each dose of doxorubicin (cumulatively 20 mg/kg ip, for 28 days). The animals' whole-body, liver, and kidney weight, serum biochemical examination, as well as microscopic examination of bone marrow, peripheral blood, liver, and kidney, were done on day 56 of the study. Hepatic and renal alterations were carefully quantified by semiquantitative grading scales-hepatic and renal damage score, respectively. In amifostine-pretreated rats, the number of peripheral blood leukocytes was significantly higher in comparison to doxorubicin-only treated group, preferentially protecting neutrophils. In the same group of rats, hepatic and renal alterations associated with polymorphonuclear cell infiltrates were significantly less severe than those observed in animals receiving only doxorubicin. Our results showed that amifostine successfully protected rats against multiple-dose doxorubicin-induced toxicity by complex, and still not fully elucidated mechanisms of action.
Keywords: Male; Rats, Wistar; orgánová specificita; Doxorubicin; Animals; potkani Wistar; Kidney Diseases; bone marrow; hepatotoxicity; amifostine; doxorubicin; mužské pohlaví; Amifostine; krysa rodu Rattus; Chemical and Drug Induced Liver Injury; Rats; lékové postižení jater; amifostin; rats; zvířata; nemoci ledvin; Organ Specificity; nephrotoxicity